Development of Modified Monopoly Game as a Learning Media On Endocrine System (Research and Development at Senior High School 1 Jakarta) - Herdani, Tresna Puspa; Sartono, Nurmasari; Evriyani, Dian (Universitas Negeri Jakarta, 2015)
Monopoly is one of the games that can be applied as a learning media. Modifications of this media were applied so this game intended to informed teacher about students’ cognitive ability and to increase students’ learning stimulus acceptance. The aim of this research was to develop modified monopoly game as learning media on endocrine system. The research was held at Senior High School 1 Jakarta using research and development method. Need assessment, product development, and try-out and revision were the steps in this research. In the try-out and revision step, media expert and material expert were involved as the assessors, meanwhile Biology teacher, and students grade XI at Senior High School 1 Jakarta were performed as the media user. After the whole try out process, the product received the lowest score was 72,67%, and the highest was 94,63%. And the average score was 85,66% that achieved a very good interpretation. The result of this research showed that the modified monopoly game could be utilized as one of learning media on Endocrine System at Senior High School grade XI science.